2019
DOI: 10.1016/j.ijid.2019.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and trends of influenza incidence in mainland China: A population-based surveillance study from 2005 to 2015

Abstract: To investigate epidemiological features and trends of influenza incidence with 1,173,640 cases in mainland China from 2005 to 2015. Methods: Incidence and mortality data for influenza from 2005 to 2015 were provided by the data-center of China public health science and covered a population of about 1.3 billion people from 31 provinces and regions in mainland China. Joinpoint regression and exploratory spatial data analyses were used to examine the incidence trends from 2005 to 2015. Results: The first upsurge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The possible explanations for these data encompass both media reporting, which emphasized that the first organ to be attacked by SARS-CoV2 and the most likely organ to fatally fail is the lungs (2), combined with more general patient anxiety. An additional factor that may have contributed to reduced respiratory consultations is that restrictions, including wearing masks and social distancing, may have reduced the rate of other respiratory infections, such as the common cold and influenza, which would normally be increased during the winter months in China (46). Unfortunately, our data do not contain sufficient detail to evaluate this possibility in the context of the Tongren Hospital outpatient clinics.…”
Section: Discussionmentioning
confidence: 91%
“…The possible explanations for these data encompass both media reporting, which emphasized that the first organ to be attacked by SARS-CoV2 and the most likely organ to fatally fail is the lungs (2), combined with more general patient anxiety. An additional factor that may have contributed to reduced respiratory consultations is that restrictions, including wearing masks and social distancing, may have reduced the rate of other respiratory infections, such as the common cold and influenza, which would normally be increased during the winter months in China (46). Unfortunately, our data do not contain sufficient detail to evaluate this possibility in the context of the Tongren Hospital outpatient clinics.…”
Section: Discussionmentioning
confidence: 91%
“…Although the NHC provides information on suspected and confirmed cases, only data from confirmed cases was used in this analysis, to avoid confusion of routine seasonal influenza cases with nCoV. 13 Confirmed cases were analysed using by applying four different estimation techniques, to allow for different assumptions about epidemic growth and the epidemiology of the disease:…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians complete a standard case report card when they identify any probable, clinical, or laboratory-confirmed case of seasonal influenza-A and influenza-B. Then, the local epidemiologists do a field investigation when they receive the disease card using a standardized form, which improves the data accuracy [16,19].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that there was a trend of increasing influenza incidence from 2005 to 2015, in mainland China [16]. China has a population of about 1.3 billion people, and the disease burden caused by influenza is still heavy.…”
Section: Introductionmentioning
confidence: 99%